Nipah Virus Outbreak in Kerala State, India Amidst of COVID-19 Pandemic - Yadav, Pragya D.; Sahay, Rima R.; Balakrishnan, Anukumar; Mohandas, Sreelekshmy; Radhakrishnan, Chandni; Gokhale, Mangesh D.; Balasubramanian, R.; Abraham, Priya; Gupta, Nivedita; Sugunan, A. P.; Khobragade, Rajan; George, Kalpana; et al. (Frontiers in Public Health, 2022)
We report here a Nipah virus (NiV) outbreak in Kozhikode district of Kerala state, India which had caused fatal encephalitis in a 12-year-old boy and the outbreak response which led to the successful containment of the disease and the related investigations. Quantitative real-time RT-PCR, ELISA based antibody detection and whole genome sequencing were performed to confirm the Nipah virus infection. Contacts of the index case were traced and isolated based on risk categorization. Bats from the areas near the epicentre of the outbreak were sampled for throat swabs, rectal swabs and blood samples for Nipah virus screening by real time RT-PCR and anti-Nipah virus bat IgG ELISA. Plaque reduction neutralization test was performed for the detection of neutralizing antibodies. Nipah viral RNA could be detected from blood, bronchial wash, endotracheal secretion and cerebrospinal fluid and anti-NiV IgMantibodies from the serum sample of the index case. Rapid establishment of an onsite NiV diagnostic facility and contact tracing helped in quick containment of the outbreak. NiV sequences retrieved from the clinical specimen of the index case formed a sub-cluster with the earlier reported Nipah I genotype sequences from India with more than 95% similarity. Anti-NiV IgG positivity could be detected in 21% of Pteropus medius and 37.73% of Rousettus leschenaultia. Neutralizing antibodies against NiV could be detected in P.medius. Stringent surveillance and awareness campaigns needs to be implemented in the area to reduce human-bat interactions and minimize spill over events which can lead to sporadic outbreaks of NiV.